Chemical characterization of activated carbon derived from Napier grass, rubber wood, bamboo, and hemp - Pongpiachan, Siwatt; Khruengsai, Sarunpron; Pripdeevech, Patcharee; Pongnailert, Suwichien; Chanlek, Narong; Thumanu, Kanjana; Muangmora, Rattana; Rojviroon, Thammasak (International Journal of Renewable Energy Development, 2024)
This study examines the process and analysis of activated carbons that use H2SO4, H2O2, and NaOH as activating agents. The distinct chemical methods employed by each activator impacted the ash and carbon content, surface properties, and functional groups of the activated carbons, exhibiting notable disparities. The ash level varied from 6.86% to 37.08%. H2SO4-activated carbons had the lowest ash content, suggesting better elimination of inorganic contaminants. The iodine number, which serves as a measure of adsorption capacity, was consistent among all samples, with values ranging from 800 to 950 mg g-1. This indicates that the three activating agents effectively increased the surface area and porosity. The BET surface areas varied between 9.14 and 167.42 m2 g-1, whereas the BJH adsorption surface areas ranged from 9.68 to 28.89 m2 g-1. The pore volumes ranged from 0.0071 to 0.0595 cm2 g-1, while the sizes ranged from 0.51 to 8.2 nm. These measurements suggest the presence of both micropores and mesopores. The FTIR spectra exhibited comparable functional groups among all samples, such as OH, CH, C=C, and C-O. The SEM-EDX and XPS tests showed that there was a lot of carbon. The carbon content was highest in H2O2-activated carbons because they were exposed to less severe oxidative conditions. These activated carbons comply with the requirements set by IUPAC and ASTM. They are suitable for catalytic processes and liquid adsorption, such as water and wastewater treatment. Subsequent research should aim to improve activation conditions to get the highest possible carbon content and optimise surface characteristics.